👤

d)5(2x-3) - 3(x+1) [tex]\geq[/tex] 4(x-9)
e) 3(x-1) - 6 < 2(x+7)
f) 5(x-1) - 3 < 3(x+4)
g) 6(x-2) + x [tex]\leq[/tex] 5(x+4)
h) 4(x+3) - 9 [tex]\leq[/tex] 3(x-1)


Răspuns :

Răspuns:

d). 10x-15-3x-3>=4x-36

7x-18>=4x-36

7x-4x>=18-36

3x>=-18

x>=-6

e). 3x-3-6<2x+14

3x-2x<14+9

x<23

f). 5x-5-3<3x+12

5x-3x<12+8

2x<20

x<10

g). 6x-12+x<=5x+20

7x-5x<=20+12

2x<=32

x<=16

h). 4x+12-9<=3x-3

4x-3x<=-3-3

x<=0

Explicație pas cu pas:

Răspuns:

Explicație pas cu pas:

d)5(2x-3) - 3(x+1)≥4(x-9)

10x-15-3x-3≥4x-36

7x-4x ≥ 18-36

3x ≥ -18

x ≥ -6    ⇒     x∈[-6, +∞)

e) 3(x-1) - 6 < 2(x+7)

3x-3-6<2x+14

3x-2x<14+9

x<23   ⇒    x∈(-∞, 23)

f) 5(x-1) - 3 < 3(x+4)

5x-5-3<3x+12

5x-3x<12+8

2x<20

x<20/2

x<10      ⇒     x∈(-∞, 10)

g) 6(x-2) + x ≤ 5(x+4)

6x-12+x≤5x+20

7x-5x ≤ 20+12

2x ≤ 32

x ≤32/2

x ≤16    ⇒   x∈(-∞, 16]

h) 4(x+3) - 9 ≤ 3(x-1)

4x+12-9 ≤ 3x-3

4x-3x ≤ -3-3

x ≤ -6    ⇒    x∈(-∞, -6]